Efeito da manipulação do feedback da percepção subjetiva de esforço esperada na percepção subjetiva de esforço e no desempenho de adultos de diferentes faixas etárias - Serafim, Thais Helena Sayegh [UNESP] (2014)
Perceived exertion (PE) is an important tool used to regulate the intensity of physical exercise. Studies have been demonstrating strong association between performance and PE. Among the factors that influence PE and performance, there are the psychological ones. Besides, the responses during physical exercise can be different according to age group. Thus, the aim of this study was to verify the manipulation effects of expected PE feedback on PE and performance in adults of different ages. Twelve young adults (23.5 ± 3.6 years) and 12 older adults (69.8 ± 5.3 years) were recruited to perform five sessions of treadmill walking exercise. The first session was an incremental test to determine the ventilatory threshold (VT) of the participants. The other four sessions (reference, deflation, control and inflation) consisted of a constant load test (VT intensity) during the first 30 minutes, followed by an incremental load (slope increase) until exhaustion. In the reference session participants reported their PE (reference PE) in the Borg Scale (6-20) every three minutes (constant load), and every minute (incremental load). The remaining sessions were divided into deflation, control and inflation of PE, in a randomized order. In these sessions, the PE of the participants was reported by the researcher every three minutes during the constant load. The reported PE was two values below, equivalent or two values above in relation to the reference PE for the deflation, control and inflation sessions, respectively. Participants were asked to agree to the reported value or report another value of PE. During the incremental load, participants reported their own PE every minute. PE and physiological responses were measured during the tests, and analyzes were separated by age group. Two-way repeated measures ANOVA was used to analyze PE and physiological responses, with the condition and moment defined as the factors. Oneway repeated measures ANOVA was...